PKM- PENERAPAN METODE CIBEST BAGI SANTRI PP AL-MUBAROK DALAM RANGKA DERADIKALISASI - Basrowi Basrowi; Nurhasan Nugroho; Endang Purwaningsih; Ajeng Eka Nurkholifah; Eka Fitriani; Eva Muti’ah; Juwita Juwita; Anita Nurjanah (Gapenas Publisher, 2023)
Terrorists are a serious threat that can endanger the safety of the nation and the state and national interests at any time. The emergence of terrorism is due to an ideology or ideology that is contrary to Pancasila and Islamic teachings, the hallmark of radicalization is synonymous with violence. An understanding like this can certainly attack any group, one of which is among students or santri who are prone to understanding radicalism. For this reason, it is necessary to socialize deradicalism to overcome radical understanding. The research objectives were 1) increasing understanding of deradicalization, 2) increasing loyalty to the Unitary State of the Republic of Indonesia, 3) increasing the activeness of students through entrepreneurial activities and 4) applying the CIBEST method. The method used in this service is the counseling and outreach method. The results of the dedication show that there was a positive impact on the training activities on PP Al-mubarok students, there was an increase in students' understanding of deradicalization and an increase in the quality of students through the CIBEST method towards students who were innovative , peace-loving and nationalist